(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
JCO is a restaurant and franchise specializing in donuts, frozen yogurt, and coffee. JCO Donuts & Coffee is owned and managed by Johnny Andrean Group, inspired by Dunkin Donut. The restaurant produces different shapes and flavors, with a particular focus on the quality of basic ingredients and the production process. With this product, JCO has attracted many customers. This research conducted what variables influence purchasing decisions. For this reason, variables in the marketing mix are determined, namely product, price, place, and promotion which are thought to influence purchasing decisions. This study uses primary data, using a questionnaire. The respondents of this study were JCO customers, who were randomly assigned to 250 respondents. The analytical tool used is multiple regression by first testing the validity and reliability of the data. The results of the study indicate that the product, price, place, and promotion have positive and significant influence, both partially and simultaneously on purchasing decisions.